Extração e pré-concentração em linha de flúor em águas e determinação pelo Metódo de Spadns - Rocha, Diego Pessoa (2015)
This work developed a flow system for pre-concentration and determination of fluoride by molecular absorption spectrophotometry using SPADNS method in water samples. The method is based on the reaction of fluoride ions with the complex zirconium and the trisodium salt of 1,8-dihydroxy-2- (4-sulfophenylazo) -naphthalene-3,6-disulphonic acid (SPADNS), leading to discoloration. The samples were pre-concentrated in a Tygon® minicolumn tube with 5 cm long and 2.0 mm internal diameter, containing Layered Double Hydroxides (NO3.Mg-Al LDH) used as adsorbent for the retention of fluoride ions. Thereafter, the fluorine ions were eluted with sodium hydroxide 0.5 mol L-1 and determined by SPADNS method. The flow system was constructed of solenoid valves, in order to improve analytical performance, as each independent valve injects the solutions so leading to a more efficient use of the reagents. The variables that affect the system such as the mass of adsorbent, type of eluent, eluent flow rate and pre-concentration, SPADNS concentration and pH effect were evaluated. The material was characterized by a variety of techniques, including Mid-Infrared Spectroscopy (FT-MIR) and Scanning Electron Microscopy (SEM). Surface area and the average diameter of the particles was also determined. The results of the optimal conditions, selected with the compromise between sensitivity and the analytical speed, was mass of adsorbent 150 mg; pre-concentration flow rate 3 mL min-1; elution flow rate 1 mL min-1, using as the eluent sodium hydroxide 0.5 mol L-1; hydrochloric acid concentration in SPADNS 1.8 mol L-1. The detection limit was 15 ug L-1, the limit of quantification of 50 ug L-1, relative standard deviation of 0.8 %, linear range of 50-500 ug L-1 and pre-concentration factor of 10.3. The accuracy of the method was evaluated by analysis of certified material ALPHA APS 1076 (Simulated Rain Water), the values were not significantly different at a 95% level of confidence with the certified value. The method was applied in the analysis of water and the levels found were below the maximum values established by Brazilian regulation.